Kepuasan Belajar Warga Belajar Pada Program Kesetaraan Paket C - Kartini Marzuki; Rudi Amir (Seminar Nasional LP2M UNM, 2019)
Abstract. The equality program as an alternative in solving school problems In addition to economic factors, besides the economic factors, one of the factors that influence the dropout rate is about the low learning motivation of students who are the target group of equality programs.. This study aims to reveal: (1) the level of learning satisfaction related to teacher competence in the learning process, (2) the level of learning satisfaction of the learning population towards teacher competence in the application of learning methods. This research is an ex-post facto research using correlational techniques. The research population was 176 people that studying in the equivalency learning group of package C guided by the non-formal education unit of the Sawerigading Study Program in Makassar. Sampling through the stratified random sampling technique which was subsequently determined was 88 people. The results of data analysis show that: (1) the level of learning satisfaction is calculated with the ability of the tutor to understand the students in the learning process by 47%. (2) learning satisfaction related to the application of learning methods by tutors by 71%. Thus, it can be denied that learning satisfaction related to Andragogical Tutor's competency is still in the fairly temporary category in applying the learning method that already in the Good category Keywords: Equality Program, Learning Satisfaction, tutor competence